World water '89 managing the future, learning from the past : proceedings of an international conference organized by the Institution of Civil Engineers and held in London on 14-16 November 1989. (Thomas Telford, 1990)
The supply of wholesome drinking water throughout the world is an issue of fundamental importance. However, population growth and the pollution of many supplies means that increased management of resources is required. This book looks at the lessons of the past and the options for the future.
Keywords: Water-supply engineering.; Sewage disposal.; elektronické knihy; electronic books